ISSUES OF LEGAL CULTURE, LEGAL CONSCIOUSNESS AND LEGAL MENTALITY IN KAZAKHSTANI SOCIETY (Journal of actual problems of jurisprudence, 2023)
Effective functioning of all elements is important for the legal system. The legal system is a system capable of changing its own structure in the course of activity. The article is devoted to the study of legal culture, legal consciousness and legal mentality in Kazakhstani society. Low level of legal consciousness and legal culture leads to the weakening of the legal culture of the society and the instability of the legal system. Concepts, mutual influence, important elements of legal mentality, legal consciousness and legal culture were studied in the article. The need to study the interaction of these legal phenomena contributes to a deep understanding of the structure of the legal mentality in Kazakhstani society. At the same time, the issues of legal mentality, legal culture and legal awareness should be considered comprehensively, taking into account the mental characteristics of citizens in society and their general value system. This is one of the important directions of national legal science. Development of social and cultural values of the society is one of the most important tasks in the context of creating a legal state.The result of the research is the development of concrete proposals for the effective functioning of the national legal system, the development of legal mentality, legal culture and legal consciousness from today's point of view, and the development of measures to deeply understand the directions and laws of their interaction.Keywords: legal mentality, legal culture, legal consciousness, legal regulation